Translation Strategies of Tautology in Chinese Political Discourse - A Case Study of Xi Jinping: The Governance of China (Volume III) - Huang, Mengyan; Xie, Zenan (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Tautology, as a rhetorical device characterized by repetition and emphasis, enhances the appeal, authority, and logical clarity of Chinese political discourse. It holds considerable rhetorical and pragmatic value and plays a significant role in the international dissemination of China’s political narrative. This article begins by examining the concept, structure, and function of tautology, and then analyzes the translation strategies used to render tautological expressions from Chinese into English. Particular attention is given to the strategies of simplification, substitution, and generalization. Drawing on real-world translation practices, the study identifies a shared goal among these strategies: reducing redundancy and streamlining sentence structure to produce translations that are clearer, more logical, and more culturally adaptable. By applying translation theory to the analysis of political discourse, this article aims to offer practical insights for the cross-cultural communication of Chinese political thought in an international context.